Determinants of User Acceptance of the Digilib Application at the UIN Sunan Kalijaga Yogyakarta Library - Jihan Dhiya Faridah; Nafisah, Syifaun; Nazrul Effendy (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
The Digilib application represents an innovative library service aimed at extending access to a wider community. However, its utilization remained low, prompting this study to examine the factors influencing the acceptance of digital library technology. This research employed a quantitative design with a correlational approach, analyzing data collected from 68 Library Science students at UIN Sunan Kalijaga Yogyakarta through questionnaires. The primary data were processed using SmartPLS 3 to evaluate dimensions of the Technology Acceptance Model (TAM), including Perceived Ease of Use, Perceived Effectiveness, Attitude Toward Use, Behavioral Intention to Use, and Actual System Usage. The findings revealed that user acceptance of the Digilib application was significantly influenced by factors such as Digilib’s branding, its flexibility in integrating with external information sources, the quality of information provided, and its user-friendly design. Enhancing these aspects could improve the adoption rate of the Digilib application, thereby enabling libraries to achieve their goal of extending services to a broader audience.